1997
DOI: 10.1128/jcm.35.11.2759-2761.1997
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of skin by Helcococcus kunzii

Abstract: In order to investigate the role of Helcococcus kunzii as a colonizer of skin and as a possible participant in diabetic foot ulcers, we used a selective medium to culture both lower-and upper-extremity skin from a study group of podiatry patients (60 diabetics and 60 nondiabetics) and a control group of 50 healthy volunteers. Although differences in colonization were not statistically significant, a trend toward higher colonization rates in the group of podiatry patients was noted. H. kunzii appears to prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
2
16
0
Order By: Relevance
“…Demonstration of enhanced growth in broth supplemented with 0.1% Tween 80 offers further support for this identification. Like other reports (2,4,8), biochemical testing of our isolate resulted in API profile no. 4100413.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Demonstration of enhanced growth in broth supplemented with 0.1% Tween 80 offers further support for this identification. Like other reports (2,4,8), biochemical testing of our isolate resulted in API profile no. 4100413.…”
supporting
confidence: 84%
“…The fermentation of inulin and the failure to ferment trehalose in conventional media observed for the case isolate are atypical for this species both in our experience and in previous reports (2,8). Laboratories using the API 20S Strep system (2,4,8) have reported this species as inulin negative and an acidifier of trehalose, but one investigator (4) also noted acidification of inulin for an isolate which they called "Helcococcus-like." Failure to ferment trehalose in unsupplemented heart infusion-based media has been reported previously (2).…”
supporting
confidence: 59%
“…Helcococcus kunzii is a part of normal skin fl ora usually found in the lower limbs [2,5,6] . It can cause opportunistic infections mostly in immunocompromised patients.…”
Section: Discussionmentioning
confidence: 99%
“…Host risk factors are also important; diabetes and vascular insuffi ciency are associated with colonization of lower limbs with H. kunzii [5,6] . A study on the incidence of skin colonization demonstrated that 10% (12/120) of the foot specimens collected from podiatry patients, twothirds of whom were diabetic, were positive for H. kunzii [6] . In our patient we believe that uncontrolled diabetes was the major risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Helcococcus kunzii is a facultative anaerobic bacterium that was first described by Collins et al in 1993, and was initially considered as a commensal of the human skin [ 1 3 ]. Recent reports of invasive infections caused by H. kunzii indicate that this microorganism has to be considered as an opportunistic pathogen that can be involved in severe infections in human [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%